2018
DOI: 10.3791/56947
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing Lignification Dynamics in Plants with Click Chemistry: Dual Labeling is BLISS!

Abstract: Lignin is one of the most prevalent biopolymers on the planet and a major component of lignocellulosic biomass. This phenolic polymer plays a vital structural and protective role in the development and life of higher plants. Although the intricate mechanisms regulating lignification processes in vivo strongly impact the industrial valorization of many plant-derived products, the scientific community still has a long way to go to decipher them. In a simple three-step workflow, the dual labeling protocol present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…Subsequent confocal fluorescence microscopy observation indicates that S CP 6 is incorporated in a time‐ and dose‐dependent manner into the lignifying walls of differentiating secondary xylem cells but is not/poorly incorporated into already lignified mature cell walls (Figure ). This labelling pattern is in agreement with our previous observations of the alkyne‐ and azide‐tagged G‐ and H‐unit reporters 4 and 5 , respectively . Additional experiments showed that S CP incorporation is 1) abolished by competition with the natural S monolignol 3 and 2) almost completely eliminated in samples when the enzymatic machinery is heat denatured prior to incubation, indicating that S CP incorporation is under enzymatic control (see Figures S3 and S4).…”
Section: Figuresupporting
confidence: 91%
See 2 more Smart Citations
“…Subsequent confocal fluorescence microscopy observation indicates that S CP 6 is incorporated in a time‐ and dose‐dependent manner into the lignifying walls of differentiating secondary xylem cells but is not/poorly incorporated into already lignified mature cell walls (Figure ). This labelling pattern is in agreement with our previous observations of the alkyne‐ and azide‐tagged G‐ and H‐unit reporters 4 and 5 , respectively . Additional experiments showed that S CP incorporation is 1) abolished by competition with the natural S monolignol 3 and 2) almost completely eliminated in samples when the enzymatic machinery is heat denatured prior to incubation, indicating that S CP incorporation is under enzymatic control (see Figures S3 and S4).…”
Section: Figuresupporting
confidence: 91%
“…Results showed that DAR inv is orthogonal to the other two reactions as S CP is fully converted into the corresponding dihydropyridazine cycloadduct while H AZ and G ALK remain untouched. After full conversion of S CP , specific SPAAC cycloaddition between H AZ and DBCO‐PEG 4 ‐Rhodamine Green occurs without degradation of either the S CP cycloadduct or of the remaining G ALK reporter in the mixture, and can in turn be linked to TAMRA‐azide by CuAAC as previously reported . Based on these results we developed an in vivo, sequential triple‐labelling protocol to visualize lignification in flax plant cell walls.…”
Section: Figurementioning
confidence: 60%
See 1 more Smart Citation
“…Chemical reporters H az , G alk and S cp were synthesized as previously described [ 36 , 61 , 62 ]. Natural and tagged monolignols were metabolically incorporated in the plant samples at a final concentration of 5 µM for 20 h ( Figure S5 ).…”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile, lignin is an aromatic polymer formed via enzymatic radical coupling of several tautomeric isomers of phenylpropanoid monolignols [ 18 ]. Lignin in wood absorbs ultraviolet light and endows the wood architecture with hydrophobicity through accumulation between the cell walls, known as lignification [ 18 , 19 ]. Lignin is also enzymatically degraded by the action of white-rot fungi [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%